Eight Years Experience of Transanal Endoscopic Microsurgery - Hosseini, Seyed Vahid; Rezazadehkermani, Mohammad; Algharah, Ali Abdulridha Abbas; Bananzadeh, Alimohammad; Shahidinia, Seyedeh Saeideh; Haghazali, Mehrdad (Journal of Coloproctology, 2023)
Introduction Transanal Endoscopic Microsurgery (TEM) is a minimally invasive method for management of different proctologic conditions. Despite widespread use of this method, it is not used widely in Iran. This report is about to describe the application of TEM in managing different proctologic conditions in a tertiary colorectal referral center in Iran regarding methods and complications.Methods All of the patients' documents such as procedure, method, early postop complications and further operations were actively reviewed and the data were entered in to the database.Results Since 2012 till the end of 2020 chart review was done and 150 cases of TEM operation were found. The most frequent procedure that was done was resection procedure. Using different energy devices during surgery or suturing versus not suturing the defect were not associated with complication. There was a case of in hospital mortality and one case delayed perianal fistula following TEM. Measurement of lesion distance from anal verge was not significantly different using TEM or colonoscopy. Villous adenomas detected in colonoscopy were mostly associated with malignancy. In evaluated resected lesions most of cases had free base and distance from anal verge or using different energy devices were not associated with obtaining free base.Conclusion TEM is a safe minimal invasive procedure with acceptable complications that could be helped in managing different proctologic conditions and the results of reviewing our patients revealed the same results that is reported from other colorectal centers.
Keywords: transanal endoscopic microsurgery; postoperative complications; suture techniques; cautery; fistula; colonic polyp